A General Principle for DUV NLO Materials: π‐Conjugated Confinement Enlarges Band Gap - Xiong, Lin; Wu, Li‐Ming; Chen, Ling (Angewandte Chemie International Edition, 2021)
Current nonlinear optical materials face a conventional limitation in the trade‐off between the band gap and birefringence, especially in the deep UV spectral region. To circumvent this dilemma, we propose a general principle, π‐conjugated confinement, to partially decouple the interunit π‐conjugated interactions by the separation of non‐π‐conjugated units. The goal is to further enlarge the band gap to a value larger than that of the singular π‐conjugated counterpart and to maintain a suitable density of π‐conjugated units to gain a large optical anisotropy. We reveal that π‐conjugated confinement is a shared structural feature for all DUV NLO materials known to date, and thus, it provides a novel and essential design criterion for future design synthesis. Guided by this principle, the carbonophosphates are predicted to be a new promising DUV candidate system. Sr3Y[PO4][CO3]3 (1) and Na3X[PO4][CO3] (X=Ba, Sr, Ca, Mg, 2–5) exhibit not only greatly enhanced birefringence that is 3–24 times larger than that of singular phosphates but also enhanced band gaps that are 0.2–1.7 eV wider than those of singular carbonates. We propose a general principle, π‐conjugated confinement, for the rational design of high‐performance DUV NLO materials whose band gaps are further enhanced. This principle is valid for all the DUV NLO materials known to date (the Chinese lunar year of the ox). Guided by this approach, the carbonophosphates are discovered for the first time as new DUV NLO candidates. Sr3Y[PO4][CO3]3 exhibits the shortest SHG output laser among phosphates to date.